Experimental Investigation of an Index-Mismatched Multiphase Flow Using Optical Techniques. (12th February 2013) - Coronado Diaz, H.; Hugo, Ronald J.
Abstract : An experimental investigation of multiphase flow involving a liquid (water) and a gas (air) is performed. The results for three different scenarios are presented: fixed bubble, ascending bubble, and dispersed-bubble turbulent pipe flow. This study involves a comparison of statistical data collected using two sensing systems, a wavefront sensor and a high-speed video camera. A signal analysis technique based on signal attenuation is developed for data collected using the wavefront sensor. The three experiments performed provide experimental evidence that the Shack-Hartmann wavefront sensor, operating on signal attenuation, is a viable method for the study of multiphase bubble flows.